Peculiarities of Cryptocurrency Circulation and Fiscal Aspects of Crypto Transactions: An Overview of Domestic and Foreign Practices - Krykhivska Nataliia О.; Romashko Oleksandra M.; Grebeniuk Nadiia V.; Markiv Mariia M. (Problemi Ekonomiki)
The aim of the article is to study and analyze the current state of legislation regarding the regulation of cryptocurrency assets in Ukraine and, taking into account foreign experience, to identify recommendations for improving domestic legislative initiatives to ensure the transparency, security, and efficiency of the cryptocurrency market. To achieve this aim, comparative analysis, synthesis, and generalization of the obtained data were used. The main hypothesis is that efficient regulation of cryptocurrencies can improve the economic stability of the country. It is identified that cryptocurrencies require a comprehensive approach to regulation, considering global experience and the specifics of national legislation. The research methodology involved analyzing existing regulatory acts, studying cryptocurrency regulation practices in individual countries, and conducting a comparative analysis. The assessment of legal lacunae and the development of recommendations for improving Ukrainian legislation were the main objectives. An assessment of the current state of cryptocurrency regulation in Ukraine is carried out, a comparative analysis of international experience is presented, and proposals for improving legislation are formulated. Issues related to the taxation of cryptocurrencies are characterized, and major directions for the development of this sphere in Ukraine are allocated. The theoretical significance of this research lies in clarifying concepts and categories related to cryptocurrencies and their regulation, as well as in analyzing scientific approaches to solving legal problems. The practical significance is the development of recommendations for improving national legislation, which will contribute to the development of the cryptocurrency market. The originality of the research consists in comparing Ukrainian legislation with international standards and identifying new approaches to cryptocurrency regulation. The main conclusions concern the necessity of improving the legislative framework and developing specific legal mechanisms for effective control of this area.